The coast-to-coast murders - Patterson, James, 1947-; Barker, J. D. (Jonathan Dylan), 1971- (Little, Brown and Company, 2020)
A baffling string of murders throughout the country leads Detective Garrett Dobbs and FBI Agent Jessica Gimble to the family of two Ivy League intellectuals who raised their adopted children in a traumatizing experimental environment.